Mekanisme Pembatasan Penanaman Modal Asing Dalam Bidang Perkebunan Menurut Hukum Positif Di Indonesia - Anna Stephanie; Kartina Pakpahan; Yolanda Natalia Isabel; Gandace Siregar (Mahesa Research Center, 2020)
Foreign investment in Indonesia in the plantation sector has a positive impact on national development. The need for encouragement and support in the plantation business by creating policies,which one is able to increase foreign investment in the plantation business. The purpose of this research is to analyze from the perspective of the prevailing law in Indonesia and to find out the factors that hinder the restriction of foreign investment in the plantation sector. This study uses a normative juridical method, namely by using a qualitative approach. The conclusion of this study is that the mechanism for limiting foreign investment in the plantation sector is regulated in Law Number 25 of 2007 concerning Foreign Investment and Law Number 39 of 2014 concerning Plantations, where these regulations must be considered by foreign investment in investing in plantation sector in Indonesia. The factors that hinder foreign investment are the usual business actors bribing State officials, the problem of being limited to opening a business entity because the land acquisition process is too long.